2007
DOI: 10.1111/j.1574-6968.2007.00924.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel leptospiral protein increases ICAM-1 and E-selectin expression in human umbilical vein endothelial cells

Abstract: It has been reported previously that activation of vascular endothelium by outer membrane proteins of the spirochetes Borrelia sp. and Treponema sp. resulted in enhanced expression of endothelial cell adhesion molecules. To investigate the role of leptospiral proteins in this process, a predicted lipoprotein encoded by the gene LIC10365 was selected, which belongs to a paralogous family that presents a domain of unknown function, DUF1565. The LIC10365 gene was cloned and the protein expressed in Escherichia co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
1
11

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 36 publications
2
24
1
11
Order By: Relevance
“…Recently, a group of investigators described that the OMP of Leptospira can induce endothelial cell damage in vitro. 12 To the best of our knowledge, this study is the first to disclose endothelial glycocalyx injury in human leptospirosis. Interestingly, these alterations could be seen, even in milder forms of leptospirosis.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Recently, a group of investigators described that the OMP of Leptospira can induce endothelial cell damage in vitro. 12 To the best of our knowledge, this study is the first to disclose endothelial glycocalyx injury in human leptospirosis. Interestingly, these alterations could be seen, even in milder forms of leptospirosis.…”
Section: Discussionmentioning
confidence: 83%
“…10 The outer membrane proteins (OMPs) of Leptospira are capable of promoting up-regulation of cell adhesion molecules (for instance, intercellular adhesion molecule-1 [ICAM-1]) expressed mainly in endothelial cells. 11,12 Although these studies were performed in vitro with umbilical vein endothelial cells, they suggested a role of endothelial activation in leptospiral pathogenesis. 11,12 Also, experimental and autopsy studies have shown endothelial necrosis and capillary thrombosis in lung tissue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18,20,21 and for the pathogenic L. interrogans. 23,25 In this work, we report for the first time a L. interrogans protein, genome annotated as hypothetical, that is capable to bind laminin and fibronectin ECM components and to activate the endothelial CAM, E-selectin. The protein encoded by the LIC12690 gene is predicted to be an outer/inner membrane 29 and to be a lipoprotein.…”
Section: Discussionmentioning
confidence: 96%
“…22 We have shown that the recombinant protein rLIC10365 of L. interrogans promoted upregulation of intercellular adhesion molecule 1 (ICAM-1) and E-selectin on HUVECS. 23 More recently, we reported that three selected coding sequences (LIC10507, LIC10508 and LIC10509), located in a region of the L. interrogans serovar Copenhageni genome that has a potential involvement in pathogenesis, 24 were also capable to promote stimulation of ICAM-1 and E-selectin on monolayers of HUVECS. 25 We trust that understanding the molecular mechanism of leptospiral pathogenesis should help the identification of novel vaccine candidates.…”
Section: Introductionmentioning
confidence: 98%